Billy and Oliver: an approach to promoting resilience and improving interaction in two residential child care settings - Charlotte Wilson; John Mackland; Jessica Cundy (Scottish Journal of Residential Child Care)
We are writing this paper as practitioners at Barnardo's Linksfield Service in Aberdeen, and Barnardo's Caern Project in Edinburgh. Barnardo's Linksfield Service provides a residential environment for children who display emotionally and socially challenging behaviour and/ or have experienced multiple placement disruptions, whose circumstances prevent chem from being accommodated with foster carers or their birch family. Barnardo's Caern Project is a residential shore breaks unit for young people with learning disabilities, and provides a support at home service which aims to increase the resilience and confidence of parents and carers.